The Equality of Believers. Protestant Missionaries and the Racial Politics of South Africa, Richard Elphick: book review - Kritzinger, J. J. (Faculty of Theology, University of the Free State, 2013)
Abstract not available
Elpphick, Richard. 2012. The Equality of Believers. Protestant Missionaries and the Racial Politics of South Africa. Charlottesville: University of Virginia Press, 2012. 437pp, hardback ISBN 978-0-8139-3273-6.
Keywords: Book reviews